What Are the Ethical Guidelines for AI Clinical Research? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
Artificial intelligence (AI) is rapidly and profoundly reshaping the landscape of clinical research. From accelerating drug discovery and development to enab...
Keywords: AI Ethics in Healthcare; Ethical; Guidelines; Clinical; Artificial Intelligence; Healthcare; Patient Care